STRATEGI KESANTUNAN DALAM DEBAT CAWAPRES PERIODE 2014 s.d. 2019 DI TV ONE BERDASARKAN PENDEKATAN BROWN DAN LEVINSON: STRATEGI KESANTUNAN DALAM DEBAT CAWAPRES PERIODE 2014 s.d. 2019 DI TV ONE BERDASARKAN PENDEKATAN BROWN DAN LEVINSON - Nur Ainun Makkiyah; Taufik Nurhadi (Universitas PGRI Adi Buana Surabaya, 2015)
This research is motivated by the fact that the use of languageis polite to the people who have an important role for Indonesia it is very important due to the smoothness and harmony and to establish intimacy between the narrator and the opponent. The formulation of the problem in this research is